Optimizing cutting parameters for cutting power and roughness in VAT 32® turning with an experimental Al2O3method - Kondo, Marcel Y [UNESP] (2018)
The development of new materials for manufacturing of combustions engines grows as environmental regulations increase. New technologies related to combustion have been developed, causing higher working temperatures inside the engine, which increases the requirements on the materials in the construction of the engines. The superalloy VAT 32® was developed to replace the superalloy UNS N07751 in the manufacturing of valves for combustion engines. This work analyzed the turning of VAT 32® with an experimental Al2O3-MgO-based ceramic cutting tool developed by the authors. The properties of the experimental ceramic cutting tool are relative density of 98.50 ± 0.12%, hardness of 19.28 ± 0.16 GPa and KIC of 4.7 ± 0.5 MPa m-1/2. It were analyzed the cutting powers and the superficial roughness of the workpiece during machining by a data acquisition system. It was evaluated the influence of the following cutting parameters: cutting speed, feed and depth of cut. nal array, it was found the combinations of the cutting parameters searching for better roughness and cutting power response. The influence of feed and depth of cut were significant in the response of cutting power. When analysing the influence in the response of superficial roughness, only the cutting parameter feed showed significance. Optimizing the cutting parameters, for better roughness, the cutting speed found was 400 m/min, feed of 0.1 mm/rot and 0.25 mm for depth of cut. The lesser cutting power was found for machining with cutting speed of 500 m/min, feed of 0.1 mm/rot and 0.25 mm for depth of cut. The tests showed the viability use of the experimental ceramic tool in VAT 32® machining.